2011
DOI: 10.1126/science.1200832
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Electrocatalysts for Oxygen Reduction Derived from Polyaniline, Iron, and Cobalt

Abstract: The prohibitive cost of platinum for catalyzing the cathodic oxygen reduction reaction (ORR) has hampered the widespread use of polymer electrolyte fuel cells. We describe a family of non-precious metal catalysts that approach the performance of platinum-based systems at a cost sustainable for high-power fuel cell applications, possibly including automotive power. The approach uses polyaniline as a precursor to a carbon-nitrogen template for high-temperature synthesis of catalysts incorporating iron and cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

87
3,046
9
36

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 3,820 publications
(3,200 citation statements)
references
References 30 publications
87
3,046
9
36
Order By: Relevance
“…The activity gap between the state‐of‐the‐art Pt/C (E‐TEK) and the Fe‐N‐rGO‐900°C catalyst, as reflected by a difference of half‐wave potential (Δ E 1/2 ) in RDE testing, has been substantially reduced to ≈60 mV (0.85 vs 0.79 V). The measured ORR activity in acidic media is comparable to that of advanced NPMCs 9. The Fe‐N‐rGO‐900 °C catalyst also demonstrates superior ORR activity in comparison to Fe‐N‐KJ‐900 °C and N‐rGO‐900 °C catalysts (Figure 5c).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The activity gap between the state‐of‐the‐art Pt/C (E‐TEK) and the Fe‐N‐rGO‐900°C catalyst, as reflected by a difference of half‐wave potential (Δ E 1/2 ) in RDE testing, has been substantially reduced to ≈60 mV (0.85 vs 0.79 V). The measured ORR activity in acidic media is comparable to that of advanced NPMCs 9. The Fe‐N‐rGO‐900 °C catalyst also demonstrates superior ORR activity in comparison to Fe‐N‐KJ‐900 °C and N‐rGO‐900 °C catalysts (Figure 5c).…”
Section: Resultsmentioning
confidence: 60%
“…On the other hand, high stability of the Fe‐N‐rGO‐900 °C catalyst is demonstrated in potential cycling tests (Figure 5d). The cycling was carried out within a potential range of 0.6 to 1.0 V in nitrogen‐saturated 0.5 m H 2 SO 4 at a scan rate of 50 mV s −1 9. No significant activity loss was observed in the ORR kinetic region of Fe‐N‐rGO‐900 °C catalyst even after 10 000 cycles, attesting to the high durability of the developed catalysts in acidic electrolyte.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We also demonstrated that FeN x C y moieties and Fe@N‐C species are moderately active toward PRR, proving their possible roles in both direct (major path) and indirect 4 e − ORR pathways. Since the synthesis of Fe‐N‐C catalysts with only FeN x C y moieties,10b, 15 only Fe@N‐C particles,10a or their combination3b,3d, 17 is now controllable, the understanding of the nature of active sites for PRR provided herein offers new insights for the rational design of advanced Fe‐N‐C catalysts with high selectivity and expectedly improved durability in polymer electrolyte fuel cells. …”
mentioning
confidence: 99%
“…Very recently, a variety of N-doped carbon catalysts based on PANI have been constructed which showed superior electrocatalytic activities for the ORR [7][8][9][10][11][12]. The multi-technique characterization have suggested that the enviable performance should be ascribed to the formation of metal-N complexion structures as well as the carbon nanostructures such as thin graphene sheets and nanofibers [10][11][12].…”
Section: Open Accessmentioning
confidence: 99%